The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1508/cytologia.81.447
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Meiotic Behavior in <i>Eremurus himalaicus</i> Baker (Liliaceae): A Rare Endemic Perennial from Kinnaur, Himachal Pradesh, India

Abstract: Summary Detailed meiotic studies have been carried out in 11 accessions of Eremurus himalaicus Baker belonging to family Liliaceae an endemic medicinal plant of the Northwestern Himalayas. E. himalaicus, due to its excessive exploitation for edible uses, is living under stress and has therefore been listed in the Red Data Book of Indian Plants as a rare species. Considering x=7 as the basic chromosome number for the species, E. himalacus revealed the diploid chromosome count of 2n=14. Out of 11 populations wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(27 reference statements)
2
0
0
Order By: Relevance
“…Somatic chromosome analysis of eight species of Aloe (Asphodelaceae) showed diploid chromosome number of 2n = 14 (Sánchez-Get al 2018). The other species of the genus growing in India, i.e., E. himalaicus is also diploid with chromosome num-ber of 2n = 14 (Kumari et al, 2016). In present study meiotic abnormalities were found in the target species, similarly meiotic abnormalities were also found in E, himalaicus growing in Indian Himalayan region (Kumari et al, 2016).…”
Section: Reproductive Outputsupporting
confidence: 65%
See 1 more Smart Citation
“…Somatic chromosome analysis of eight species of Aloe (Asphodelaceae) showed diploid chromosome number of 2n = 14 (Sánchez-Get al 2018). The other species of the genus growing in India, i.e., E. himalaicus is also diploid with chromosome num-ber of 2n = 14 (Kumari et al, 2016). In present study meiotic abnormalities were found in the target species, similarly meiotic abnormalities were also found in E, himalaicus growing in Indian Himalayan region (Kumari et al, 2016).…”
Section: Reproductive Outputsupporting
confidence: 65%
“…The other species of the genus growing in India, i.e., E. himalaicus is also diploid with chromosome num-ber of 2n = 14 (Kumari et al, 2016). In present study meiotic abnormalities were found in the target species, similarly meiotic abnormalities were also found in E, himalaicus growing in Indian Himalayan region (Kumari et al, 2016). The abnormalities are attributed to pervading environmental conditions in the Himalaya (Wani et al 2023).…”
Section: Reproductive Outputsupporting
confidence: 61%